MEMBANGUN KESADARAN HUKUM PADA MASA PANDEMI COVID – 19 MELALUI PENGEMBANGAN RENCANA PELAKSANAAN PEMBELAJARAN - Rahmanu Wijaya; Warsono Warsono; Nanik Setyowati; Maya Mustika Kartika Sari (SUPREMASI HUKUM, 2021)
The President of the Republic of Indonesia has established the status of a health emergency in the Presidential Decree 11 of 2020, as well as stated in Presidential Decree 12 of 2020 that non-natural disasters caused by COVID-19 as a national disaster. The consequence is the birth of the role of the government through legal instruments and actions to control the community, so it is important to build legal awareness. In this case teachers have the authority to form a Learning Implementation Plan (RPP) applied to students, then this legal research aims to know the authority of teachers of Pancasila education and citizenship (PPKn) junior high school (SMP) in drafting RPP to build legal awareness during the covid-19 pandemic. The method used is Statute Approach, which is based on the legislation on the authority of teachers and related to the status of health emergencies and non-natural disasters. The results showed that PPKN teachers have the authority to develop RPP that builds legal awareness for students, especially with regard to the control exercised by the government during the pandemic. Keywords: PPKn Teacher, RPP, Legal Awareness